2005
DOI: 10.1182/asheducation-2005.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Complications of Sickle Cell Disease: Role of Nitric Oxide and Hemolytic Anemia

Abstract: Medical advances in the management of patients with sickle cell disease, thalassemia, and other hemolytic anemias have led to significant increases in life expectancy. Improved public health, neonatal screening, parental and patient education, advances in red cell transfusion medicine, iron chelation therapy, penicillin prophylaxis for children, pneumococcal immunization, and hydroxyurea therapy have all likely contributed to this effect on longevity. 1,2 Importantly, as a generation of patients with sickle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 63 publications
4
75
0
1
Order By: Relevance
“…Prior studies of PH in Hb-SS have revealed an association of PH with a history of renal dysfunction and an elevation in ALT (28,38). In addition, platelets appear to have an important role pathogenically in the development of PH, both as mediators of serotonin metabolism and in their role in thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of PH in Hb-SS have revealed an association of PH with a history of renal dysfunction and an elevation in ALT (28,38). In addition, platelets appear to have an important role pathogenically in the development of PH, both as mediators of serotonin metabolism and in their role in thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…64 A PH prevalence of 60% to 75% has been reported in both thalassemia intermediate and major, 10 and occurs in nearly every form of hereditary or acquired hemolytic anemia. 8,55 PH has been definitively linked to hemolytic rate and low NO bioavailability in both human and sickle cell transgenic mouse studies. 8 Hsu and colleagues have dem- Figure 4.…”
Section: Vascular Phenotypes Of Sickle Cell Diseasementioning
confidence: 99%
“…As such, LDH represents a convenient biomarker of intravascular hemolysis and NO bioavailability associated with mortality that Kato and colleagues found helpful in identifying the clinical subphenotypes of hemolysis-associated vasculopathy ( Figure 5). 54 PH is the best characterized clinical complication of acute and chronic hemolysis 55 and occurs in about one third of adults 7,22,56 and children [57][58][59][60][61] with SCD. A Doppler echocardiogram measured tricuspid regurgitant jet velocity (TRV) of 2.5 m/sec or greater, suggesting PH is currently the strongest predictor for early death in SCD, with approximately 10-fold increased risk of early mortality 7,62,63 and a 40% mortality risk within 3 years of diagnosis.…”
Section: Vascular Phenotypes Of Sickle Cell Diseasementioning
confidence: 99%
“…Intravascular hemolysis (1/3 of SCD hemolysis) and extravascular hemolysis are driven by HbS polymerization and HbS instability respectively (Bensinger and Gillette, 1974;Hebbel, 2010). Recent evidence suggests that chronic intravascular hemolysis is associated with a state of progressive vasculopathy, characterized by reduced nitric oxide (NO) bioavailability, prooxidant and pro-inflammatory stress, coagulopathy, pulmonary hypertension, stroke, leg ulcers, and priapism (Gladwin and Kato, 2005;Gladwin et al, 2004;Kato et al, 2007;Morris et al, 2008;Reiter et al, 2002).…”
Section: Hemolytic Crisismentioning
confidence: 99%